Comparison and evaluation of the efficacy of compressed SENSE (CS) and gradient‐ and spin‐echo (GRASE) in breath‐hold (BH) magnetic resonance cholangiopancreatography (MRCP) - He, Ming; Xu, Jin; Sun, Zhaoyong; Wang, Shitian; Zhu, Liang; Wang, Xiaoqi; Wang, Jiazheng; Feng, Feng; Xue, Huadan; Jin, Zhengyu (Journal of magnetic resonance imaging, 2020)
Contract grant sponsor Chinese Academy of Medical Sciences (CAMS) Initiative for Innovative Medicine; Contract grant number: 2017‐I2M‐1‐001; Contract grant sponsor: Outstanding Youth Fund of Peking Union Medical College Hospital; Contract grant number: JQ201704; Contract grant sponsor: National Natural Science Foundation of China; Contract grant number: 81871512; Contract grant sponsor: National Public Welfare Basic Scientific Research Program of Chinese Academy of Medical Sciences; Contract grant numbers: 2018PT32003 and 2017PT32004. Background Both compressed‐sensing (CS) and gradient‐ and spin‐echo (GRASE) sequences can achieve 3D magnetic resonance cholangiopancreatography (MRCP) with a single breath‐hold (BH). This work hypothesized that compared with conventional navigator‐triggered (NT)‐MRCP, the two BH‐MRCP protocols, GRASE and CS, may provide better imaging quality, especially for patients with irregular breathing. Purpose To evaluate and compare the image quality and diagnostic performance of three MRCP protocols. Study Type Prospective. Subjects Seventy‐four patients suspected to have duct‐related pathologies were enrolled. Field Strength 3.0T. Sequences NT‐MRCP, BH‐CS‐MRCP, and BH‐GRASE‐MRCP. Assessment Breath regularity was evaluated subjectively according to the respiratory waves. The acquisition time was compared. The pancreaticobiliary system was divided into 12 segments and evaluated on a 5‐point scale. The diagnostic performance of the three MRCPs was evaluated and compared. Statistical Tests The Friedman test with a post‐hoc test, receiver operating characteristic (ROC) curve analysis, McNemar test, and Kendall's W test were used. Results The BH‐MRCP decreased the scan time significantly (P < 0.05). The overall imaging scores of GRASE‐MRCP and CS‐MRCP were significantly higher than that of NT‐MRCP for patients with irregular breathing (4.283 and 4.283 vs. 3.000, both P < 0.05). Compared with NT‐MRCP, the diagnostic performance of BH‐CS and BH‐GRASE MRCP was significantly improved for patients with irregular breathing (AUC = 0.860 and 0.863 vs. 0.572, both P < 0.001). Data Conclusion Compared with conventional NT‐MRCP, the overall imaging quality and diagnostic performance of BH‐CS and BH‐GRASE MRCP were not significantly different for patients with regular breathing and significantly superior for patients with irregular breathing. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2020;51:824–832.